MANAJEMEN KEPALA SEKOLAH DALAM IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH MENENGAH PERTAMA (SMP) - Zalikha, Zalikha; Iskandar, Iskandar; Danil, M. (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The study aims to: (1) analyze the principal's management planning for differentiated learning, (2) analyze the principal's management organization for differentiated learning, (3) analyze the principal's management execution in implementing differentiated learning, and (4) analyze the principal's management supervision in differentiated learning. This qualitative research was conducted at SMPN 4 Tanah Luas and SMPN 1 Tanah Luas in North Aceh Regency, with principals, teachers, and supervisors as informants. Data were collected through interviews, observations, and documentation. The findings are: (1) The principal's planning for differentiated learning is effective, involving staff in training, facilitating infrastructure, and ensuring classroom comfort. Teachers gather information on students' talents and learning styles. (2) The principal's organization for differentiated learning is effective, involving staff in creating organizational structures and assigning tasks based on qualifications and expertise, including forming peer learning groups. (3) The principal's execution of differentiated learning is effective, providing digital tools despite challenges. (4) The principal's supervision of differentiated learning is effective, involving scheduled supervision, teacher reflection, feedback, and discussions on professional development, though challenges exist.